1982
DOI: 10.1007/bf00287281
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in attributions and learned helplessness

Abstract: This investigation assessed the hypothesis that girls are more likely to be learned helpless in math than boys. Students in grades 5 through 11 completed questionnaires assessing their causal attributions for success and failure in mathematics, their self-concepts of math ability, and their expectations for both current and future success in math. Results indicated that sex differences in attributions depended on the type of methodology used (open-ended or rank-ordered questions). The most consistent differenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
53
0
5

Year Published

1987
1987
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(63 citation statements)
references
References 26 publications
(23 reference statements)
4
53
0
5
Order By: Relevance
“…As was found in previous research (Basow & Medcalf, 1988;D'Amico, Baron & Sissons, 1995;Erkut, 1983;Ickes & Layden, 1978;LaNoue & Curtis, 1985;Parsons, Meece, Adler & Kaczala, 1982;Little & Lopez, 1997;Rustemeyer & Jubel, 1996;Wiegers & Frieze, 1977), females compared to males favored effort attributions ("paid attention" and "studied"), whereas males used more ability attributions than females for successful outcomes, especially for the masculine subject matter. For failure outcomes, however, males more than females thought that a lack of studying and low interest was responsible.…”
Section: Evidence For Gender Differencessupporting
confidence: 58%
See 1 more Smart Citation
“…As was found in previous research (Basow & Medcalf, 1988;D'Amico, Baron & Sissons, 1995;Erkut, 1983;Ickes & Layden, 1978;LaNoue & Curtis, 1985;Parsons, Meece, Adler & Kaczala, 1982;Little & Lopez, 1997;Rustemeyer & Jubel, 1996;Wiegers & Frieze, 1977), females compared to males favored effort attributions ("paid attention" and "studied"), whereas males used more ability attributions than females for successful outcomes, especially for the masculine subject matter. For failure outcomes, however, males more than females thought that a lack of studying and low interest was responsible.…”
Section: Evidence For Gender Differencessupporting
confidence: 58%
“…Some of the research suggests that women display a less self-enhancing pattern of causal attributions than men. Women have been found to attribute successful outcomes more externally (Feather, 1969;Meehan & Overton, 1986;Pasquella, Mednick & Murray, 1981;Simon & Feather, 1973;Viaene, 1979;Zuckerman, 1979) or more to effort rather than ability than men (Erkut, 1983;Ickes & Layden, 1978;Parsons, Meece, Adler & Kaczala, 1982;LaNoue & Curtis, 1985;Wiegers & Frieze, 1977). For failures, males see internal causes, especially a lack of ability, as less important than do females, thereby protecting their self-esteem (Basow & Medcalf, 1988;D'Amico, Baron & Sissons, 1995;Ickes & Layden, 1978;LaNoue & Curtis, 1985).…”
Section: Gender Differences In Causal Attributionsmentioning
confidence: 92%
“…In general, these studies indicate that women tend to underrate their skills or performance as compared to men (Wohlers and London, 1989;Lindeman et al, 1995). This underrating has been attributed to the fact that women often do not take credit for success, attributing success to external sources or luck rather than to effort or ability (Rosenthal et al, 1996;Parsons et al, 1982;LaNoue and Curtis, 1985). Moreover, Rosenthal et al (1996) argue it may be 'proper female modesty' accounting for the underrating by female managers.…”
Section: Gender and Self-perceptions In Business And Entrepreneurshipmentioning
confidence: 99%
“…Accordingly, it is possible to say that female and male teachers have close scores to each other in both overall classroom management and its sub-dimensions. Previous studies on classroom management emphasize that gender is an important variable creating difference (Amin, 1994;Ekici, 2008;Erol, 2006;Grossmann, 1990;Güvenç, 2012;İlgar, 2007;Martin & Yin, 1997;Özgan et al, 2011;Parsons, 1982;Savran & Çakıroğlu, 2004;Van Oostendorp, 1991;Zeremba & Fluck, 1995). However, our results indicated that there is no statistical difference between the teachers' attitude and belief levels regarding classroom management and its sub-dimensions by gender (Ekici, 2008;Ekici et al, 2012;Denkdemir, 2007;Okut, 2011;Savran Gencer & Çakıroğlu, 2007).…”
Section: Conclusion and Discussionmentioning
confidence: 99%